Impact of Information Sharing on Adoption and User Satisfaction among the Wearable Device Users - Vaidik Bhatt, Samyadip Chakraborty, Tulika Chakravorty (International Journal of Control and Automation, 2020)
In the current lifestyle, where most of the population is suffering from lifestyle disorders, remaining fit is important. It is also said that, remaining fit is equivalent to remaining healthy. There are IoT enabled wearable devices available which tracks the fitness and gives vital information to the users. The study empirically analyses the impact of information sharing capability of such devices on Adoption of such devices with rigorous methodology of Partial Least Square – Structural Equation Modelling using responses from 238 respondents. The study concludes that, information sharing capability of IoT plays a vital role in adoption of such devices which is moderated by self-efficacy of user. Study gives theoretical and practical implications for future research as well as managers for developing such devices.